Validity and reliability of the 3-meter backward walk test in mildly disabled persons with multiple sclerosis - Bilek, Furkan; Demir, Caner Feyzi (Elsevier Sci Ltd, 2022)
Background: One of the biggest problems for persons with Multiple Sclerosis (PwMS) is dizziness, poor posture, and balance problems that cause injury-causing falls. The aim of our study was to reveal the test-retest reliability and validity of the 3-Meter Backward Walk Test (3MBWT) in mildly disabled PwMS. Methods: This study included a total of 93 mildly disabled PwMS with mean EDSS of 1.89. 3MBWT, Functional Access Test (FRT), Dynamic Gait Index (DGI), Timed 25-Foot Walk (T25FW), and Timed-Up and Go (TUG) were applied to the patients. To measure test-retest reliability, a second evaluation was performed three days after the first evaluation. Results: Cronbach's alpha coefficient was found to be 0.998 (excellent). For intra-rater agreement, the ICC values in the individual test were 0.998. The SEM value was 0.18, the MDC value was found to be 0.50. A very strong correlation was revealed between the 3MBWT and FRT (r:-0.931, p: 0.001), TUG (r: 0.968, p: 0.001), T25FW (r: 0.879, p: 0.001), DGI (r:-0.871, p: 0.001) and falling history (r: 0.932, p: 0.001). Conclusion: The 3MBWT was observed to be valid and reliable in mildly disabled PwMS. 3MBWT is an effective and reliable tool for measuring ability to walk backward in mildly disabled PwMS.
Keywords: Backward walking; 3-Meter Backward Walk Test; Falls; Balance; Validity; Reliability